NEW INSIGHTS ON EARLIEST DEVONIAN (LOCHKOVIAN) OSTRACODS FROM THE ARGENTINE PRECORDILLERA (Ameghiniana, 2016)
Ostracods from the Lower Devonian (Lochkovian) of the Argentine Precordillera Basin (upper levels of the Los Espejos Formation and lowermost ones of the Talacasto Formation) were studied. These units represent one of the best Lochkovian stratigraphic records in the Malvinokaffric basins. According to this revision, records of Devonian ostracod faunas in southwestern Gondwana can be extended to older stratigraphic levels. One new genus Suinella and ten species, including five new records (Suinella huarpesi gen. and sp. nov., Amphizona? argentinensis sp. nov., Bollia talacastensis sp. nov., Petrisigmoopsis? rotundum sp. nov. and Pircawayra antiqua sp. nov.) and one reassignment (Thilpsurella aff. T. putea Coryell and Cuskley) were hereby defined. The studied taxonomic assemblage differs from younger Devonian Malvinokaffric ostracod associations by being relatively diverse and composed mainly of drepanelloideans together with metacopids. The association is characterised by species with thin and spiny carapaces, a fact suggesting a relatively deep and low-energy environment below storm wave base. The mixed palaeobiogeographic affinities of the Lochkovian ostracod fauna contrasts with the clear Malvinokaffric signature of the upper Lower–Middle Devonian associations previously recognised in Argentina. Resumen. NUEVAS PERSPECTIVAS ACERCA DE LOS OSTRÁCODOS DEL DEVÓNICO TEMPRANO (LOCHKOVIANO) DE LA PRECORDILLERA ARGENTINA. Se estudiaron los ostrácodos del Devónico Inferior (Lochkoviano) de la Precordillera Argentina (niveles superiores de la Formación Los Espejos y niveles inferiores de la Formación Talacasto). Estas unidades representan uno de los mejores registros del Lochkoviano en cuencas Malvinocáfricas. Esta revisión extiende, a niveles más antiguos, el rango temporal de los ostrácodos devónicos conocidos para el suroeste de Gondwana. Se describió un nuevo género Suinella gen. nov. y diez especies, incluyendo cinco nuevas (Suinella huarpesi gen. y sp. nov., Amphizona? argentinensis sp. nov., Bollia talacastensis sp. nov., Petrisigmoopsis? rotundum sp. nov. y Pircawayra antiqua sp. nov.) y se realizó una reasignación específica (Thilpsurella aff. T. putea Coryell y Cuskley). La asociación taxonómica descripta difiere de las asociaciones de ostrácodos devónicos Malvinocáfricos más jóvenes. La asociación es relativamente diversa y está compuesta principalmente por drepanelloideos junto con metacopidos. La asociación está además caracterizada por especies con conchillas finas y espinas. Esto sugiere un ambiente relativamente profundo y de baja energía, por debajo del nivel de base de olas de tormenta. Las afinidades paleobiogeográficas de mezcla que muestra la fauna de ostrácodos lochkovianos, contrastan con la clara afinidad Malvinocáfrica de las asociaciones del Devónico Inferior alto y Devónico Medio reconocidas previamente en Argentina.